Mengintegrasikan teknologi dalam pendidikan Islam dan mempersiapkan generasi muslim untuk masa depan - Purnama, Rizkiyah; Nasution, Abdusima (Journal of Counseling, Education and Society, 2024)
The Industrial Revolution 4.0 has introduced significant changes across various life sectors, including education. For Islamic education, technology integration is critical to remain relevant in the global era. This research explores how Islamic education can embrace modern technology such as artificial intelligence, big data, and IoT while preserving Islamic values. Using a qualitative approach, the study highlights challenges and strategies for integrating technology into Islamic education, focusing on digital literacy, curriculum development, and educator competence enhancement. The findings suggest that balanced technological and spiritual approaches are necessary to prepare a globally competitive and morally grounded Muslim generation.